Molecular identification of Proteus mirabilis, Vibrio species leading to CRISPR-Cas9 modification of tcpA and UreC genes causing cholera and UTI - Muhammad Naveed; Fatima Tahir; Tariq Aziz; Muhammad Waseem; Syeda Izma Makhdoom; Nouman Ali; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Scientific Reports, 2024)
Abstract Heavy metal accumulation increases rapidly in the environment due to anthropogenic activities and industrialization. The leather and surgical industry produces many contaminants containing heavy metals. Cadmium, a prominent contaminant, is linked to severe health risks, notably kidney and liver damage, especially among individuals exposed to contaminated wastewater. This study aims to leverage the natural cadmium resistance mechanisms in bacteria for bioaccumulation purposes. The industrial wastewater samples, characterized by an alarming cadmium concentration of 29.6 ppm, 52 ppm, and 76.4 ppm—far exceeding the recommended limit of 0.003 ppm—were subjected to screening for cadmium-resistant bacteria using cadmium-supplemented media with CdCl2. 16S rRNA characterization identified Vibrio cholerae and Proteus mirabilis as cadmium-resistant bacteria in the collected samples. Subsequently, the cadmium resistance-associated cadA gene was successfully amplified in Vibrio species and Proteus mirabilis, revealing a product size of 623 bp. Further analysis of the identified bacteria included the examination of virulent genes, specifically the tcpA gene (472 bp) associated with cholera and the UreC gene (317 bp) linked to urinary tract infections. To enhance the bioaccumulation of cadmium, the study proposes the potential suppression of virulent gene expression through in-silico gene-editing tools such as CRISPR-Cas9. A total of 27 gRNAs were generated for UreC, with five selected for expression. Similarly, 42 gRNA sequences were generated for tcpA, with eight chosen for expression analysis. The selected gRNAs were integrated into the lentiCRISPR v2 expression vector. This strategic approach aims to facilitate precise gene editing of disease-causing genes (tcpA and UreC) within the bacterial genome. In conclusion, this study underscores the potential utility of Vibrio species and Proteus mirabilis as effective candidates for the removal of cadmium from industrial wastewater, offering insights for future environmental remediation strategies.